1989
DOI: 10.1111/j.1399-6576.1989.tb02956.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycopyrrolate: pharmacokinetics and some pharmacodynamic findings

Abstract: In the present study, a sensitive and reproducible radioreceptor assay (RRA) was used to evaluate the basic pharmacokinetic properties of glycopyrrolate, a quaternary amine with peripheral antimuscarinic activity. Based on the plasma levels after a single intravenous injection, 6 micrograms/kg (n = 6), the distribution phase half-life (2.22 +/- 1.26 s.d. min) and the elimination phase half-life (0.83 +/- 0.29 h) of glycopyrrolate were short due to the low distribution volume during the elimination phase (0.64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 24 publications
3
26
2
Order By: Relevance
“…Its vagal blockade persists for two to three hours. It crosses the placental barrier to a limited extent compared with atropine [11,12], with peak fetal concentrations about 4% of maternal concentrations following IV administration in pregnant dogs. Of note, glycopyrrolate interacted with β-agonist drugs for asthma in this trial, inducing significant tachycardia in several parturients.…”
Section: Discussionmentioning
confidence: 99%
“…Its vagal blockade persists for two to three hours. It crosses the placental barrier to a limited extent compared with atropine [11,12], with peak fetal concentrations about 4% of maternal concentrations following IV administration in pregnant dogs. Of note, glycopyrrolate interacted with β-agonist drugs for asthma in this trial, inducing significant tachycardia in several parturients.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, glycopyrrolate was administered intramuscularly 15 min before the induction of spinal anesthesia based on the heart rate response following intramuscular injection. 11,18 As a result, clinically significant tachycardia was not observed in patients receiving glycopyrrolate. Additionally, no significant difference was observed in the recorded incidence of bradycardia between the two groups.…”
Section: 414mentioning
confidence: 90%
“…When glycopyrrolate is administered intravenously, heart rate increases within one minute. 11 This abrupt tachycardia could be serious in elderly patients, particularly patients with cardiovascular disease. 24 On the other hand, the use of an intramuscular injection of glycopyrrolate can be an alternative approach to prevent the occurrence of abrupt tachycardia and can gradually counteract the hypotensive responses following spinal anesthesia.…”
Section: 414mentioning
confidence: 99%
“…Pharmacokinetic studies have shown a rapid mean distribution phase half-life (2.22G1.26 minutes), with peak plasma concentrations achieved in less than 4 minutes for intravenous administration. 8 Like the tertiary amines scopolamine and atropine, glycopyrrolate is a nonselective muscarinic antagonist. 9 Glycopyrrolate is approved by the US Food and Drug Administration for use in anesthesia and in the treatment of peptic ulcer disease.…”
Section: Discussionmentioning
confidence: 99%